2015
DOI: 10.1021/acs.est.5b02225
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Aerosol Optical Thickness Derived from MODIS and in Situ Ground Datasets over Jaipur, a Semi-arid Zone in India

Abstract: The first detailed seasonal validation has been carried out for the Moderate Resolution Imaging Spectroradiometer (MODIS) Terra and Aqua satellites Level 2.0 Collection Version 5.1 AOT (τMODIS) with Aerosol Robotic Network (AERONET) Level 2.0 AOT (τAERONET) for the years 2009-2012 over semi-arid region Jaipur, northwestern India. The correlation between τMODIS versus τAERONET at 550 nm is determined with different spatial and temporal size windows. The τMODIS overestimates τAERONET within a range of +0.06 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…AOD is a crucial parameter to estimate air quality. So, the level 3.0 collection version 6.1 monthly mean AOD data at 550 nm wavelength is extracted from MODIS for the study period (Payra et al, 2015;Kang et al, 2016). More details about the retrieval techniques and concepts can be found elsewhere…”
Section: Moderate Resolution Imaging Spectro-radiometer (Modis)mentioning
confidence: 99%
“…AOD is a crucial parameter to estimate air quality. So, the level 3.0 collection version 6.1 monthly mean AOD data at 550 nm wavelength is extracted from MODIS for the study period (Payra et al, 2015;Kang et al, 2016). More details about the retrieval techniques and concepts can be found elsewhere…”
Section: Moderate Resolution Imaging Spectro-radiometer (Modis)mentioning
confidence: 99%
“…The Jaipur site (26.91 °N, 75.78 °E) is on the eastern edge of the Thar Desert, flanked on three sides by the Aravalli Mountains [33,58,59]. It is India's most populous city having 3.1 million populations.…”
Section: Synoptic Meteorology and Methodsmentioning
confidence: 99%
“…For example, Ginoux et al [25] found that, while DB based AOD values were within the standard deviation of AERONET data in Africa, the Arabian Peninsula, and India, they were overestimated in California, Australia, and Israel. Payra et al [26] observed dependence of estimation accuracies on Monsoon in a semi-arid urban region in India. In 2013, the second generation of DB (as part of Collection 6) was proposed [27], which used a hybrid approach to account for inhomogeneously vegetated urban/built-up areas among other improvements.…”
Section: Datasets Usedmentioning
confidence: 99%